HEPATOPROTECTIVE AND NEPHROPROTECTIVE EFFECTS OF THE AQUEOUS EXTRACT OF TURMERIC (CURCUMA LONGA) IN RIFAMPICIN AND ISONIAZID-INDUCED HEPATOTOXICITY AND NEPHROTOXICITY IN RATS - M THUAWAINI, MAHDI; AL-FARHAAN, MAWAHIB B GASIM; F ABBAS, KARIMA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The present study was designed to estimate the influences of oral administration of aqueous extract of turmeric (Curcuma longa) in hepatotoxicity and nephrotoxicity induced in rats by isoniazid and rifampicin (RIF) for 4 weeks. Influences were determined through the estimation of liver and kidney functions and histopathological changes. Materials and Methods: A total of 48 male albino rats were randomly divided into six groups: Normal control, INH+RIF treated rats, Turmeric aqueous extract 100 mg/kg treated rats, Turmeric aqueous extract 100 mg/kg + INH and RIF treated rats, Turmeric aqueous extract 200 mg/kg treated rats, Turmeric aqueous extract 200 mg/kg+ INH and RIF treated rats. Turmeric aqueous extract and INH + RIF (50 mg/kg bwpo, daily) were given for 4 weeks. Liver and kidney function markers (aspartate transaminase [AST], alanine transaminase [ALT], alanine phosphatase [ALP], bilirubin, blood urea, and creatinine) were determined enzymatically. In addition, tissues of liver and kidney were quickly separated and fixed in 10% formalin and subjected to histopathological studies. Statistical analysis was carried out using t-test. Results: The aqueous extract of turmeric (at a dose of 100 and 200 mg/kg bw, p.o. daily ) showed hepato- and reno-protective effects in hepato- and reno- toxicity induced by RIF and INH in rats. Significant elevation of serum ALT, AST, ALP, total bilirubin, creatinine, urea, and total protein, due to RIF and INH treatment, were significantly decreased. The histopathological study further confirmed the biochemical results. Conclusion: Results of the present study indicated that turmeric has hepatoprotective and renoprotective action against RIF- and INH-induced hepatic and renal injury in rats.